Social reproduction: the sidelined aspect in gender and agricultural research - Kawarazuka, Nozomi; Hoa, P.T.; Huyen, L.T.T; Trang, B.; Achandi, Esther L. (Frontiers Media, 2023)
Introduction: This study explores women’s agribusiness by employing feminist theories to gain an understanding of the gender dimension of business beyond economic value, including non-material and non-market aspects associated with social reproduction.